2014
DOI: 10.1111/joca.12051
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Health Consciousness and Familiarity with DTCA on Perceptions of Dietary Supplements

Abstract: This study examines the effect of consumer health-consciousness on attitude toward dietary supplements as well as consumer perceptions of supplement risks and benefits when compared to their prescription drug counterparts. The authors investigate three conditions (insomnia, depression, and high cholesterol) with both a prescription drug and dietary supplement regimen available. Results indicate that health consciousness is positively related to attitudes toward dietary supplements, which is positively related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…These sequential relationships underscore the importance of following recommended health behavior changes, regardless of whether these actions are prescribed by physicians or external health resources (Makarem et al ). Thus, our study aligns with a growing literature base seeking guidance on how active decision making leads to better health and wellness (Royne et al ; Scammon et al ). We thus contribute to the literature in three ways: (1) we lend support to the link between behavioral change and perceived health and wellness, (2) we provide evidence that digital information seeking is a viable path to behavioral change and perceived health and wellness, and (3) we offer initial support that primary care physicians may play an active role in co‐creating wellness through motivating consumers' digital information seeking.…”
Section: Discussion and Consumer Welfare Recommendationssupporting
confidence: 84%
“…These sequential relationships underscore the importance of following recommended health behavior changes, regardless of whether these actions are prescribed by physicians or external health resources (Makarem et al ). Thus, our study aligns with a growing literature base seeking guidance on how active decision making leads to better health and wellness (Royne et al ; Scammon et al ). We thus contribute to the literature in three ways: (1) we lend support to the link between behavioral change and perceived health and wellness, (2) we provide evidence that digital information seeking is a viable path to behavioral change and perceived health and wellness, and (3) we offer initial support that primary care physicians may play an active role in co‐creating wellness through motivating consumers' digital information seeking.…”
Section: Discussion and Consumer Welfare Recommendationssupporting
confidence: 84%
“…As investigated by Ching-Hsu Huang [ 27 ], health consciousness does make changes to consumer preference, therefore influencing purchasing decisions of food. Numerous studies illustrate that health consciousness influences consumption [ 2 , 28 , 29 ], attitude and behavior [ 28 , 30 ], and word of mouth (WOM) [ 22 ]. However, the literature lacks information on how health consciousness influences consumers’ perceived knowledge and belief.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hong (2009), consumers maintain their health status by doing daily health activities, consuming fresh and organic food, preserving physical and psychological health in balance. The research is studied and found that consumers' attitudes are significantly and positively affected by consumers' health consciousness particularly in dietary supplement products (Royne, Fox, Deitz, & Gibson, 2014). Once state by state stay at home (health) orders are raised, e-commerce sales may alleviate at a lower growth rate than they are currently.…”
Section: Literature Reviewmentioning
confidence: 99%